2010
DOI: 10.1021/ac101849w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dioxins by Gas Chromatography/Resonance-Enhanced Multiphoton Ionization/Mass Spectrometry Using Nanosecond and Picosecond Lasers

Abstract: Dioxins in a soil sample were measured using gas chromatography/resonance-enhanced multiphoton ionization/time-of-flight mass spectrometry coupled with different types of laser sources. The fourth-harmonic emission (266 nm) of a nanosecond Nd:YAG laser (1 ns) provided low ionization efficiency, especially for highly chlorinated dioxins/dibenzofurans (CDDs/CDFs). The ionization efficiency was improved using the fourth-harmonic emission (266 nm) of a picosecond Nd:YAG laser (4 ps), due to shorter singlet excited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…However, it has been reported that the ionization efficiency can be significantly improved by replacing the fourth-harmonic emission with the fifth-harmonic emission (or the simultaneous use of both emissions) of a picosecond Nd:YAG laser. 36 Thus, a compact picosecond laser (33 × 18 × 46 cm) with a high average power would be useful for the practical trace analysis of DXNs in environmental samples, and probably in human blood as well. …”
Section: Dxnsmentioning
confidence: 99%
“…However, it has been reported that the ionization efficiency can be significantly improved by replacing the fourth-harmonic emission with the fifth-harmonic emission (or the simultaneous use of both emissions) of a picosecond Nd:YAG laser. 36 Thus, a compact picosecond laser (33 × 18 × 46 cm) with a high average power would be useful for the practical trace analysis of DXNs in environmental samples, and probably in human blood as well. …”
Section: Dxnsmentioning
confidence: 99%
“…The sample was heated at 230 C by a heater, and rapidly introduced into a linear-type TOFMS using air as the carrier gas. The MPI/TOFMS used in the present study has been reported in detail elsewhere, 19,20 and is now commercially available (HGK-1; Hikari-GK, Fukuoka, Japan). The fourth harmonic emission of a nanosecond Nd:YAG laser (266 nm, 4 ns, ~50 μJ, 10 Hz, GAIA II; Rayture Systems) was used as an ionization laser.…”
Section: Mpi/tofmsmentioning
confidence: 99%
“…The second peak is too early to be a fragment ion. The third peak has a flight time twice as long as the flight time of peak (2). It should be noted that this peak cannot be assigned to a dimmer of the compound providing peak (2), since, in time-of-flight mass spectrometry, the flight time is not proportional to the mass of the analyte, but is proportional to the square root of the mass of the analyte.…”
Section: Nitric Oxidementioning
confidence: 99%
“…When combined with gas chromatography, it is possible to detect and measure more than several hundred components at the femtogram level. [1][2][3] Since chlorinated and nitro aromatic hydrocarbons, such as dioxins and nitropyrenes, have extremely short excited-state lifetimes, it is necessary to use a femtosecond laser, because of its high efficiency of ionization. 1,3 However, the cost of such lasers is one of the most important issues in laser spectrometry, and the use of a lower-cost laser would be highly desirable in practical applications.…”
Section: Introductionmentioning
confidence: 99%